Human Resource Planning in the Digital Era: Challenges and Opportunities - Hendrina, Yolanda; Bahiroh, Eloh (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
To be able to face intense business competition along with advances in information technology today, Human Resources (HR) has become the most important aspect in a company or organization that cannot be replaced by technological advances. Digital transformation has had a significant impact on the way companies or organizations work, make decisions and operate. It seems that HR must be digitally ready in order to maintain their position in the business and revolutionize the employee experience by combining several aspects such as HR, Technology and processes in a new digital ecosystem. Therefore, proper Human Resources (HR) planning is needed in this digital era. HR planning in the digital era will be faced with significant challenges and opportunities. In order to be able to overcome challenges and take advantage of existing opportunities, the role of an HR Manager is needed who has knowledge about business and not only about business but technological expertise is also needed in HR planning in this digital era.